International trends in cancer incidence in middle-aged and older adults in 44 countries. Issue 3 (April 2022) - Pilleron, Sophie; Alqurini, Naser; Ferlay, Jacques; Haase, Kristen R.; Hannan, Michelle; Janssen-Heijnen, Maryska; Kantilal, Kumud; Katanoda, Kota; Kenis, Cindy; Lu-Yao, Grace; Matsuda, Tomohiro; Navarrete, Erna; et al.
Abstract: Objective: We examine international incidence trends of lung, colorectal, prostate, and breast cancers, as well as all cancers combined excluding non-melanoma skin cancer (NMSC) in adults aged 50 and older, over a fifteen-year period using data from 113 high quality population-based cancer registries included in the Cancer in Five Continents (CI5) series and NORDCAN. Materials and methods: We calculated annual incidence rates between 1998 and 2012 for ages 50–64, 65–74, and 75+, by sex and both sexes combined. We estimated average annual percentage change (AAPC) in rates using quasi-Poisson regression models. Results: From 1998 to 2012, incidence trends for all cancers (excluding NMSC) have increased in most countries across all age groups, with the greatest increase observed in adults aged 75+ in Ecuador (AAPC = +3%). Colorectal cancer incidence rates increased in the majority of countries, across all age groups. Lung cancer rates among females have increased but decreased for males. Prostate cancer rates have sharply increased in men aged 50–64 with AAPC between 5% and 15% in 24 countries, while decreasing in the 75+ age group in 21 countries, by up to −7% in Bahrain. Female breast cancer rates have increased across all age groups in most countries, especially in the 65–74 age group and in Asia with AAPC increasing to 7% in the Republic of Korea. Conclusions: These findings assist with anticipating changing patterns and needs internationally. Due to the specific needs of older patients, it is urgent that cancer systems adapt to address their growing number.